Development of banaba (Lagerstroemia Speciosa (L.) Pers) tea - De Jesus, Raylin Villanueva; Galvez, Flor Crisanta F. (1995)
A tea product that is acceptable to consumers and made from banaba leaves was developed. The effects of leaf maturity, blanching time (0, 3 and 6 min), drying temperature (40, 60, 80°C), and grinding time (0, 20 and 30 sec) on the sensory properties of the product were determined. Color, clarity, aroma, flavor, bitterness and astringency and overall acceptability of products were evaluated by 24 consumer panelists using 9-point hedonic scales. Blanching time and drying temperature significantly affected color and clarity of the tea produced but not the other attributes. Results indicated that a tea product that is acceptable to consumers can be made using mature leaves that were blanched for 6 min, dried at 80°C and ground for 30 sec.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tea